SEHATI (Screening and Health Education Holistic Integratif) Berbasis Multiple Intelligences Serta Young Health Leader Pada Siswa SDN Selorejo 1 - Nadia Regita Ayu Cahyani; Ijazah Ilmi Rohmah; Muhammad Syihabuddin; Lucky Radita Alma (Universitas Mataram, 2023)
SDN 1 Selorejo is still classified as a school with limited facilities. Educational support facilities include classrooms, libraries, UKS, school gardens and sanitation. The condition of educational support facilities seems to be poorly maintained, especially UKS, school gardens and sanitation due to the lack of human resources and school management related to school activities. Aspects of school and student activities and development are not well structured, activities are incidental and not sustainable. The post- pandemic new normality period is very important for implementing health holistically. The application of Multiple Intelligences allows students to explore new areas of intelligence and increase curiosity and natural talents by using the body, senses and imagination, and practice to understand promotive and preventive health concepts well. Elementary school age children will be trained to have leadership skills from an early age. This concept was developed in a holistic integrated manner due to various factors that can influence health levels in terms of host, agent and environment. The SEHATI program has 4 main activities, namely 1) Indoor Activity, 2) Health Screening (optimization of UKS), 3) Young Farmer (optimization of the environmental love program), and 4) Outdoor Activity. SEHATI activities involve the active contribution of partners to achieve goals. The SEHATI program is designed to prioritize behavior change efforts which include changing attitudes, habituating activities, and strengthening healthy behavior. With this health effort model, partners can implement health efforts well and sustainably and have awareness of the importance of implementing and understanding health efforts for children. In addition, schools can become role models for schools with effective health efforts in the elementary school segment in Indonesia